Socioeconomic status has direct impact on asthma control: Turkish adult asthma registry - Bahar Arslan; Murat Türk; Serhat Hayme; Ömür Aydin; Derya Gokmen; Gozde Koycu Buhari; Zeynep Celebi Sozener; Bilun Gemicioglu; Ismet Bulut; Sengul Beyaz; Cihan Orcen; Secil Kepil Ozdemir; et al. (Clinical and Translational Allergy)
Abstract Background Asthma is one of the most common causes of chronic respiratory disease, and countries with low socioeconomic status have both a high prevalence of asthma and asthma‐related death. Objective In this study, we aimed to determine socioeconomic levels of asthmatic patients according to a national database and investigate the effects of social markers on disease control in our region. Methods This is an analysis of data from 2053 adult asthma patients from a multicentre chart study in Turkey. Socioeconomic status (SES) data were collected from questionnaires and this form was sent to the patients via e‐mail. Parameters related to social status and poor disease control were analyzed. Results Illiteracy (OR:2.687 [95% CI: 1.235–5.848]; p = 0.013) and lower household income (OR:1,76 [95% CI: 1.002–3.09]; p = 0.049) were found as independent risk factors for hospitalization in the multivariate logistic regression analysis. Therewithal, being aged between 40 and 60 (OR: 1.435 [95% CI: 1.074–1.917]; p = 0.015), illiteracy (OR: 2.188 [95% CI: 1.262–3.795]; p = 0.005) and being employed (OR: 1.466 [95% CI: 1.085–1.847]; p = 0.011) were considered as independent risk factors for systemic corticosteroid use at least 3 days within last 1 year. Conclusion As a result of our national database, education level, household income and working status briefly socioeconomic status have impacts on asthma control. Identification of social markers in asthma and better recognition of risk factors based on the population gives us clues to provide better asthma control in the future.